Aerial View, Balandra Beaches North and South, Trinidad, W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
An aerial view show the north and south Balandra Beaches and the thick forested surrounding areas, circa 1974. The postcard is addressed to Ms. Frances Higgins, Syracuse, New York, U.S.A. Affixed to the postcard is a Trinidad and Tobago 15 cents stamp.
Colour; Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago--Balandra Bay; Coasts--Trinidad and Tobago; 1974